LEGAL ANALYSIS OF OPPORTUNITIES AND CHALLENGES IN IMPLEMENTING ISLAMIC COMMUNITY GUIDANCE CIRCULAR LETTER NO. 2 OF 2024 WITHIN INDONESIA'S MARRIAGE REGULATORY SYSTEM - Siti Nur Aisyah; Dzurrotul Muniroh Ahdaniah; Amrotus Soviah; Ahmad Muktafi (International Conference on Humanity Education and Society (ICHES), 2025)
The high divorce rate in Indonesia indicates a lack of readiness among couples to build strong household. In response, the Ministry of Religious Affairs issued Circular Letter Number 2 of 2024 from the Director General of Islamic Community Guidance concerning the enhancement of premarital counseling quality for prospective brides and grooms. This study aims to examine the legal standing of circular letter within Indonesia’s legislative system and to analyze the normative opportunities and challenges within the marriage regulatory framework. As a normative juridical study, it employs a statutory approach with descriptive qualitative analysis. The findings show that the circular is an administrative legal product not included in the formal hierarchy of legislation and is non-binding externally, However, it plays an important role in the implementation of premarital counseling. Normatively, its implementation still faces substantial barriers, includes the absence of effective coercive norms, disharmony among cross-sectoral regulations, and disparities in regional understanding. Therefore, strengthening its legal foundation through higher-level regulation, cross-agency synergy, and increased capacity of implementers is necessary to ensure the effectiveness of this policy in building family resilience.